Gender relations and organizational culture in intra-school student organizations: Socialization and development - Septi Wulandari; Esa Septian; Pradhana Hamdhallah Suryohayati; Novita Elisa Rusdiana Saputri (University of Merdeka Malang, 2025)
The urgency of this community service stems from the persistence of gender-biased organizational practices within student bodies, which risk perpetuating inequality from an early stage. Addressing this issue in schools is essential to cultivate gender-aware leadership, foster inclusive organizational cultures, and support the national agenda for gender equality in education. This community service activity aims to strengthen gender relations and inclusive organizational culture within intra-school student organizations (OSIS). Conducted at SMAN 2 Bojonegoro, the activities involved socialization sessions and Focus Group Discussions (FGDs) with OSIS members. The program emphasized the understanding of gender concepts, equality, and the development of a supportive organizational environment. Results indicate that gender stereotypes still influence the division of tasks and leadership roles among students. The discussions revealed limited understanding of gender-inclusive practices, which led to organizational inequality and conflicts. However, the intervention successfully raised awareness, with post-test evaluations showing improved perspectives on gender fairness and inclusive organizational culture. This program concludes that sustained mentoring and gender-sensitive leadership practices are essential to transform student organizations into inclusive environments. The outcomes recommend continuous gender education, inclusive policy design, and intersectoral collaboration for long-term impact.